Investigating the content and function of stress-induced extracellular vesicles in colorectal cancer - Mason, J (2021)
Despite advances in detection and treatment, the incidence of colorectal cancer (CRC), particularly in those under 40 years of age is increasing, and survival from metastatic disease remains very low. Adaptation of tumour cells to microenvironmental stresses and anti-cancer therapies is a key mechanism driving tumour progression and resistance. Extracellular vesicles (EVs) are nanosized membrane-bound vesicles, which carry rich bioactive cargoes that are able to influence and reprogramme recipient cell behaviour. In CRC, EVs are known to be potent drivers of primary tumour growth and metastasis, and have also been shown to modulate response to treatment by promoting drug resistance. The Goberdhan Group has recently shown that glutamine depletion can lead to change in EV biogenesis, including an increase in Rab11a-exosomes formed in Rab11a-positive recycling endosomes through inhibition of the nutrient-sensing kinase complex, mechanistic Target of Rapamycin Complex 1 (mTORC1). These EVs have enhanced tumorigenic function in CRC cells. Therefore, my DPhil focussed on investigating the potential pro-tumorigenic properties of these “switched” EVs in CRC cell lines in vitro and also assessing the composition of EVs in CRC patient plasma.